Fenomena Budaya Flexing Lesti – Bilar dalam Relasinya dengan Imitative Materialistis - 'Ulyah, Himmatul; Marzuki, Moh. Edi (Jurnal Ilmiah Multimedia dan Komunikasi, 2023)
One evidence of the social changes that are taking place is the phenomenon of flexing culture, which is increasingly popular on social media, especially on the YouTube platform. Leslar Entertainment's YouTube content, which features Lesti and Bilar's flexing culture, has also received a lot of attention. Rizky Bilar and Lesti Kejora's materialistic behavior shows that they have a successful life with luxury goods, which can create a sense of imitation for netizens to be able to have the same thing. This study aims to determine how the phenomenon of flexing culture on YouTube social media Leslar Entertainment in relation to materialistic imitative using Alfred Schutz's phenomenological analysis of the period January-June 2023. Using descriptive qualitative research methods. Data collection was carried out using documentation techniques and literature studies. In this study, interactive model data analysis techniques were used, namely data collection, data reduction, data presentation, conclusion verification. The results of this study indicate that the flexing culture phenomenon displayed by Lesti-Billar on YouTube Leslar Entertainment causes materialistic imitative phenomena in some of its viewers. This can be seen from the positive comments that support Leslar's flexing content and inspire netizens to do imitative. In addition to showing off, the act of flexing is also based on because motives such as seeking attention, existence, social pressure, and lack of empathy. in order to motives also influence Lesti-Billar to increase popularity, image, social status, followers, financial gain, inspiration, entertainment, brand value, and business opportunities. This phenomenon is in accordance with Alfred Schutz's phenomenological theory.Â